Effect of Graston technique versus ischaemic compression in students who developed neck pain during distance learning in Covid-19: a pilot study preceding the randomised clinical trial - Iqbal, Mushyyaida; Noreen, Hafsa; Tasawar, Tuba Ureeda; Tajammul, Khansa (Journal of the Pakistan Medical Association, 2023)
Many people experienced neck pain during Covid-19 quarantine period due to prolonged use of electronic devices for academic activities and work from home. The aim of this study was to determine the effects of Graston Technique versus Ischaemic Compression on pain, range of movement (ROM), and functional performance in students with neck pain, due to distance learning during Covid-19 pandemic. A pilot study (randomised clinical trial) was performed. Fifty-four subjects were included in the study on the basis of sample selection criteria and were divided into two groups, Group A and Group B. The outcome measures were pain, range of movement (ROM), and disability assessed by Numeric pain rating scale (NPRS), goniometry and Neck disability index (NDI) respectively. Group A received treatment with hot pack and Graston technique, while Group B received a hot pack and Ischaemic compression. ---Continue